Analsisis Peningkatan Jumlah Pasien terhadap Perkembangan Rumah Sakit Umum Bina Sehat Kabupaten Bandung - Salma Divya Ploresita; Aldy Santo Hegiarto (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Bina Sehat General Hospital Bandung Regency is a health service in Bandung Regency that has quite a lot of patients with the availability of Information Systems, Infrastructure Facilities that support services. The formulation of the problem is how the Information System is owned, how to maintain quality and what the hospital contributes to existing human resources. With the results of the study are Information Systems, Infrastructure and good service are interrelated but there are still shortcomings of infrastructure, SIMRS that hamper service. With suggestions to improve SIMRS, add existing and missing infrastructure.